The Cadmium’s presence in soils and sediments of the Río Ayampe, Province Manabí, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2014)
The cadmium’s presence in soils, water and sediments of the Río Ayampe was tested from september to december 2013, using the systematic method of grid along the river. Eleven profiles were taken, the sampling points were located at similar distances among each other. The collected samples were refrigerated until the next day, those were analized at the Research Laboratory of Natural Resources at the Faculty of Natural Sciences, University of Guayaquil. The atomic absorption spectrophotometer Perkin Elmer was used to detect the presence of cadmiun, using the technique based on analytical methods for atomic absorption spectroscopy. The following results were obtained: Values found on soils and sediments of dwells 1-2, 3-4, 4-5, 7-8, 9-10, are lower than 0.5 ppm. Samples of sediment profiles from dwells 2-3, 5-6, 6-7, 8-9, 10-11, are above 0.5 ppm, thus exceeding the permissible level for human health. Due to the neutral ph the cadmiun could not be recorded in water.
Keywords: Cadmium; Ecuador; heavy metal; pollution; Río Ayampe